The evolution and morphodynamic characteristics of shoals and troughs in Lingdingyang Bay of the Pearl River Estuary - Fu, Linxi; Zhong, Yuhang; Zhang, Ping; Niu, Lixia; Zhang, Xiaohe; Lin, Jianliang; Cai, Huayang; Yang, Qingshu (Frontiers in Marine Science, 2025)
Shoals and troughs are the fundamental geomorphological units of estuarine systems. However, their definition and morphodynamic characteristics, influenced by the complex dynamic environment, remain a critical challenge. This work introduces a depth–area spatial function as a quantitative criterion for the definition of shoals and troughs, while simultaneously elucidating their geodynamic implications. The Lingdingyang Bay (LDB) of the Pearl River Estuary serves as a case study. From 1901 to 2018, the LDB consisted of the West Shoal, Middle Shoal, and East Shoal and the West Trough and East Trough. The threshold depth of the LDB shifted from −5.75 m in 1901 to −4.75 m between 1964 and 2018. The depth–area distribution curve of the LDB exhibits two dominant peak depths (approximately 0 m and −2 m) within the shoal stable state, which categorizes shallow areas into high, medium and low tidal flats. The shoal–trough area ratio in the LDB, relative to the threshold depths, increased from 1901 to 1998, followed by a decline between 2008 and 2018, and culminated in a restoration to the level seen in 1901 (65% shoals and 35% troughs). Regional variations in dominant forces influencing shoal formation and evolution were observed by the vertical classification of the shoal state. The West Shoal is river dominated, the East Shoal is tide dominated, and the Middle Shoal reflects an interaction between riverine inflows and tides. Stabilized curves observed between 2008 and 2018 indicate that this estuary is progressively achieving new equilibrium states. The depth–area spatial function is useful for identifying shoals and troughs within various estuaries, which also provides a geomorphological framework for understanding the estuarine evolution and sediment dynamics.